Correction: The Minderoo-Monaco Commission on Plastics and Human Health - Philip J. Landrigan; Hervé Raps; Maureen Cropper; Caroline Bald; Manuel Brunner; Elvia Maya Canonizado; Dominic Charles; Thomas C. Chiles; Mary J. Donohue; Judith Enck; Patrick Fenichel; Lora E. Fleming; et al. (Ubiquity Press, 2023)
This article details a correction to: Landrigan PJ, Raps H, Cropper M, et al. The Minderoo-Monaco Commission on Plastics and Human Health. Annals of Global Health. 2023; 89(1): 23. DOI: https://doi.org/10.5334/aogh.4056.